Effects of intermittent fasting on quality of life tolerance of chemotherapy in patients with gynecological cancers: study protocol of a randomized-controlled multi-center trial - Schmidt, Mona Wanda; Brenner, Walburgis; Gebhard, Susanne; Schmidt, Marcus; Singer, Susanne; Weidenbach, Lina; Hahn, Harriett; Puzankova, Diana; Blau-Schneider, Bettina; Lehnert, Antje; Battista, Marco Johannes; Almstedt, Katrin; et al. (Frontiers in Oncology, 2023)
Fatigue is a very common side effect during intravenous chemotherapy. Unfortunately, only few effective therapeutic options are available, mostly based on daily activity. In our pilot trial we were able to demonstrate that intermittent fasting can reduce fatigue in healthy people, thus we aimed to assess the effects of the fasting dietary on quality of life during chemotherapy in patients with gynecological cancer, especially on the domain of fatigue. The IFAST trial is designed as a prospective, randomized-controlled, multi-center trial. Participation will be offered to women with gynecological cancers (breast cancer, ovarian cancer including peritoneal and fallopian tube cancers, endometrial cancer and cervical cancer) who are planned to receive intravenous chemotherapy for at least three months. Eligible patients will be randomized 1:1, stratified by tumor type and study center. Primary endpoint is the difference in mean change in fatigue, assessed with the Functional Assessment of Chronic Illness Therapy-Fatigue Scale (FACIT-FS©). Exploratory secondary endpoints will include general Quality of Life impairment, tolerance of chemotherapy, immunological changes, peripheral cell damage in blood cells, as well as tumor response to chemotherapy. There is new evidence that prolonged fasting periods of 46-96 hours during chemotherapy can positively influence the quality of life during chemotherapy. However, these fasting regiments are not feasible for many patients. Intermittent fasting could be a feasible (manageable) option for many patients to actively improve their quality of life and tolerance to chemotherapy and possibly even enhance the effectiveness of chemotherapy.Website of trial registration: https://drks.de